Lasting increases in trait mindfulness after psilocybin correlate positively with the mystical-type experience in healthy individuals - Søndergaard, Anna; Madsen, Martin Korsbak; Ozenne, Brice; Armand, Sophia; Knudsen, Gitte Moos; Fisher, Patrick MacDonald; Stenbæk, Dea Siggaard (Frontiers in Psychology, 2022)
Background: Psilocybin-induced mystical-type experiences are associated with lasting positive psychological outcomes. Recent studies indicate that trait mindfulness is increased three months after psilocybin intake, preceded by decreases in neocortical serotonin 2A receptor (5-HT2AR) binding. However, the association between psilocybin-induced mystical-type experiences and subsequent changes in trait mindfulness remains unexplored, as does the association between trait mindfulness and 5-HT2AR binding in the healthy brain. Aim: We evaluated whether psilocybin induced lasting increases in trait mindfulness in healthy volunteers, and whether the mystical-type experience was associated with this increase. We further examined the association between pre-drug trait mindfulness and 5-HT2AR binding in neocortex and frontolimbic regions. Method: Forty-six medium-high dose psilocybin sessions were conducted in 39 healthy individuals. The mystical-type experience was measured with the Mystical Experience Questionnaire (MEQ) at the end of the session. Trait mindfulness was measured using the Mindful Attention and Awareness Scale (MAAS) at baseline and three months after the psilocybin session. Thirty-two of the participants completed pre-drug [11C]-Cimbi-36 positron emission tomography (PET) to assess 5-HT2AR binding in neocortex and, post hoc, in the frontolimbic regions amygdala, frontal cortex and anterior cingulate cortex. Results: The MAAS score was significantly increased at three-month follow-up (p= 3.24 x 10-6), a change positively associated with the MEQ score (p=0.035). Although the association between pre-drug MAAS score and neocortex 5-HT2AR binding was not significant (p=0.24), post hoc analyses revealed a significant negative association between MAAS and right amygdala 5-HT2AR binding (pFWER=0.008). Conclusion: We here show that lasting changes in trait mindfulness following psilocybin administration are positively associated with intensity of the mystical-type experience, suggesting that the acute phenomenology of psilocybin facilitates a shift in awareness conducive for mindful living. We furthermore show that higher pre-drug trait mindfulness is associated with reduced 5-HT2AR binding in the right amygdala.